Pharmaceutical drug misuse: are industry of employment and occupation risk factors? - Brown, S.; Harris, Mark N.; Prendergast, J.; Srivastava, P. (Wiley-Blackwell Publishing Ltd., 2015)
We explore the misuse of pharmaceutical drugs in the Australian workforce, focusing on whether any differences exist between workers in particular industries or occupations. In terms of industry, being employed in hospitality is positively associated with pharmaceutical drug misuse, while being employed in finance, insurance and retail is inversely related. In terms of occupation, we find that being a labourer is positively related to misuse of pharmaceutical drugs, while being employed in managerial, professional, sales, clerical or administrative roles is associated with a lower tendency. Further analysis of occupational effects revealed that being in a blue-collar occupation, as a whole, is positively related to pharmaceutical drug misuse relative to white-collar employment. Moreover, being employed in higher status roles is associated with a lower likelihood of such behaviour. Our findings imply that particular workplace pressures, cultural norms and/or working conditions might be influential factors behind workers' drug misuse.